2017
DOI: 10.1177/1464884916688963
|View full text |Cite
|
Sign up to set email alerts
|

Management and resistance in the digital newsroom

Abstract: Citation: Bunce, M. (2017). Management and resistance in the digital newsroom. Journalism, doi: 10.1177/1464884916688963 This is the accepted version of the paper.This version of the publication may differ from the final published version. This article presents an ethnographic case study of a Reuters newswire bureau during a time of conflict between the management and journalists. The article outlines the strategies that management used to incentivize their journalists to change their reporting priorities. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
1
11

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(82 citation statements)
references
References 36 publications
3
67
1
11
Order By: Relevance
“…They seemed to appreciate the usefulness of an SEO strategy, and they believed that it could only benefit journalistic work by helping news articles to be found. The above results are consistent with previous studies where journalists and media owners in Greece were found to be able to adapt to technological progress, considering it useful for their profession [15,76]. It is remarkable that there were different opinions about the journalistic product and how it is affected by the SEO practices.…”
Section: The General Impact Of Seo On Journalism (Rq5)supporting
confidence: 91%
See 1 more Smart Citation
“…They seemed to appreciate the usefulness of an SEO strategy, and they believed that it could only benefit journalistic work by helping news articles to be found. The above results are consistent with previous studies where journalists and media owners in Greece were found to be able to adapt to technological progress, considering it useful for their profession [15,76]. It is remarkable that there were different opinions about the journalistic product and how it is affected by the SEO practices.…”
Section: The General Impact Of Seo On Journalism (Rq5)supporting
confidence: 91%
“…On the other hand, many people look for specific information, and their priorities area convenience, rapid access, and accuracy [11]. As internet technologies have brought about new modes of producing and consuming news content, many changes are observed in basic journalistic work processes, such as newsgathering, news production and distribution, and the way people consume news [12][13][14][15][16][17]. The journalistic profession is changing.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Bunce (2017) shows how news metrics can be used as disciplinary devices by news managers concerned with shaping news output in ways that fit desired business models. This use of metrics to identify and reward certain reporters while rebuking others becomes absorbed into newsroom cultures and affects how reporters understand what good work looks like.…”
Section: What Measureable Journalism Means For Newsmentioning
confidence: 99%
“…Étant donné leur position privilégiée d'interaction avec les publics sur les médias sociaux (Lee et Vandyke, 2015 ;Paulussen, 2012), ils sont aux premières lignes de l'actualisation des luttes pour l'attention sur ce terrain médiatique particulier en devenant responsables de la portée et de la visibilité de leurs médias sur des plateformes sociales. Les exigences de rentabilité sont particulièrement prégnantes en ce qui les concerne, étant donné la possibilité d'amasser des données extrêmement précises sur les publics rejoints (Bunce, 2017 ;Jouët, 2003 ;Stone, 2014 ;Welbers et al, 2016) pour ensuite valoriser cette attention dans une logique publicitaire. Cette dernière pose le gestionnaire de médias sociaux comme professionnel hybride, relevant à la fois du journalisme, par la valeur journalistique des contenus qu'il doit mettre en visibilité, et de la publicité, en raison des exigences de génération d'attention envers les produits diffusés (Gobeil, 2018a).…”
Section: Une Autonomie à L'ambiguïté Croissante ?unclassified